Pesantren, Tasawuf dan Hedonisme Kultural (Studi Kasus Aktualisasi Nilai-nilai Tasawuf dalam Hidup dan Kehidupan di Pondok Pesantren Modern Gontor) - BASUKI BASUKI (Jurnal Dialog, 2017)
Islamic School has the basic essence that can not be separated from the characteristics of the pesantren institution that always stress the importance of moral Akhlaqul Karimah as a guideline life of everyday society. Therefore pesantren education system has always been and always aim to develop the personality Muhsin, not just Muslims. Muhsin personality mentioned is Sufism. This is where the intersection between Sufism and Islamic schools. The essence of Sufism is pengejawan charity, while the essence of boarding schools located in the personality development of Muhsin. In this third millinium century boarding schools are in the mainstream of life of the paradigmatic capitalism, and the condition of society that have become jungle hedonism. This brief article is the result of field research has revealed how the actualization of the values of Sufism in the modern pesantren Gontor the era of global education and cultural hedonism. PesantrKEYWORDS:en, Mukmin, Muslim, Muhsin, Sufism, Cultural Hedonism